Isolasi dan Identifikasi Senyawa Seskuiterpen dari Curcuma soloensis Val. (Temu Glenyeh) - Soerya Dewi Marliyana; Muhamad Widyo Wartono; Fajar Rakhman Wibowo; Gesti Munasah (Jurnal Kimia Valensi, 2018)
Curcuma soloensis Val. is a family plant Zingiberaceae and is known as "temu gelnyeh". This plant has been used as a medicinal plant but has not been widely reported about its chemical components. Therefore, this study was carried out to isolation and identification of the chemical components of the C. soloensis Val. rhizome. Isolation was done by extraction, fractionation, and purification. The fractionation and purification of the compound were carried out using chromatography methods. The identification of the compound was determined by spectroscopic methods including 1D-NMR (1H NMR, 13C NMR) and 2D-NMR (HSQC, HMBC). Based on NMR spectra data analysis and compared with literature, the compound obtained yellow liquid was ar-turmerone (2-methyl-6- (4-methylphenyl) hept-2-en-4-on) which was a terpenoid sesquiterpene. Ar-turmerone is the first compound that found from Curcuma soloensis Val. rhizome.